Petroleum hydrocarbons in the Terengganu river estuary - Khushwant Singh a/l Charan Singh (Terengganu: Universiti Putra Malaysia Terengganu, 2014)
The concentration of hydrocarbons in water and sediment in the Terengganu River estuary were studied in the months of July, September and November 1997. 3 sampling trips (9 July 1997, 3 September 1997 and 26 November 1997) were conducted to all the 5 sampling stations established in this study.